Postoperative Axial Length Prediction Model in Children With Congenital Cataract and Intraocular Lens Implantation - Jialin Xu; Yunhui Yu; Yaqi Wang; Shenrong Zhang; Enze Liu; Wenjing Wang; Chenyuan Zhu; Jin Li (Journal of Ophthalmology)
Conclusions: This model predicts AL growth in children following congenital cataract surgery and IOL implantation, helping ophthalmologists select appropriate IOL power.